Complexidade e reconhecimento: as dinâmicas do afeto e do conflito na EaD - Fontana, Marcus Vinícius Liessem (2015)
In this thesis, I analyze how conflict and affection, as designed by the German philosopher Axel Honneth, especially in his work The Struggle for Recognition: Moral Grammar of Social Conflicts, interfere with the dynamics of a group made up of professors and pre-service teachers in e-learning. From the perspective of Complex Thought of the French sociologist Edgar Morin, I conceive the group as a complex social system. As an exploratory research, I started with the reading of the autobiographical essays wrote by the students who completed the Degree in Spanish in Federal University of Santa Maria in 2013. In those essays, I identified situations around conflicts and affective recognition experienced by the pre-service teachers, and then I selected some informants. These informants participated in narrative interviews, in which they told their respective academic trajectories. Later, I also interviewed the professors, mentioned by them in situations of affective or conflictual interaction. I analyzed all this material from the perspective of Reconstructive Hermeneutics, making the different narratives dialogue to reconstruct the situations experienced by the narrators. From this reconstruction emerges the fact that affectivity is a constant in the relations established in e-learning and we can see it as a facilitator of learning, as well as a cohesive force that tends to keep straight the complex social system. Also, emerge conflict situations. Although the conflict is not seen as something desirable, it shows potential as a maintainer of the complex social system, and it demonstrates power to stimulate new ways of thinking, to create innovative strategies of work and new dynamics of interaction between people. Innovation resulting from the conflict serves as negentropic force, which is opposed to entropy or systemic loss of energy, contributing to the longevity of this system and to obtain positive results in educational terms. I hope these findings tend to contribute to the understanding of the dynamics of relationships in e-learning, allowing its professors understand the importance of human interactions that are revealed behind the computers.